Evaluasi Kinerja Struktur Gedung Terhadap Gempa Dengan Analisis Static Non-Linear (Pushover) - Husnuto Fikri; Muhammad Zardi; Amalia Amalia (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
The research is evaluating the Banda Aceh Pratama Tax Office building, using the Pushover Analysis method which refers to the Applied Technology Council (ATC-40, 1996) using the SAP2000 program. The purpose of this study was to determine the structural performance of the Banda Aceh Pratama Tax Office building structure and to determine the pattern of building collapse after pushover analysis. A pushover analysis was carried out because this building is located in an earthquake-prone area based on the 2017 earthquake map on SNI 03-1726-2019 with spectrum response analysis. This research was conducted using quantitative data analysis method with secondary data which includes shop drawings and structural data. Based on the results of the analysis of the response spectrum, the performance level of the structure according to ATC-40 in the structure of the x and y directions, for the maximum value of total drift obtained 0.0051 and the maximum value of total inelastic drift obtained 0.0031 so that the Banda Aceh Pratama Tax Service Office building is included in Immediate Occupancy (IO) level category based on Dt/H < 0.01 limit according to ATC-40.